Optimization of Conditions for Production of Soluble E. coli Poly(A)-Polymerase for Biotechnological Applications - Igor P. Oscorbin; Maria S. Kunova; Maxim L. Filipenko (Biology)
Poly(A) polymerase (PAP 1) from Escherichia coli is the primary enzyme responsible for synthesizing poly(A) tails on RNA molecules, signaling RNA degradation in bacterial cells. In vitro, PAP 1 is used to prepare libraries for RNAseq and to produce mRNA vaccines. However, E. coli PAP 1’s toxicity and instability in low-salt buffers complicate its expression and purification. Here, we optimized the conditions for the production of recombinant PAP 1. For that, E. coli PAP 1 was expressed in seven E. coli strains with different origins and genetic backgrounds, followed by assessment of the overall protein yield, solubility, and enzymatic activity. Among the tested strains, BL21 (DE3) pLysS achieved the best balance of cell density, total PAP 1 yield, solubility, and specific activity. Rosetta 2 (DE3) and Rosetta Blue (DE3) hosting the pRARE plasmid exhibited the lowest solubility, likely due to excessive translation efficiency. Higher induction temperatures (>18 °C) exacerbated PAP 1’s insolubility. Interestingly, PAP 1 accumulation correlated with an increase in the plasmid copy number encoding the enzyme, indicating its potential utility as a surrogate marker of PAP 1 activity. These findings provide insights into optimizing E. coli PAP 1 production for biotechnological applications.